Perceived support and perceived ability promote walking behavior in Chinese adults with chronic diseases: the mediating role of health literacy based on the COM-B model - Tang, Xue; Zhong, Xiaohua; Liu, Tian; Shi, Guiqian; Li, Kangjie; Liu, Xinjing; Zhang, Cong; Zhong, Xiaoni (Frontiers in Public Health, 2025)
BackgroundChronic diseases significantly contribute to global physical disability and mortality. Moderate-intensity aerobic activities, such as walking, are vital for managing chronic conditions. Research has shown that enhancing health literacy (HL) is crucial for promoting physical activity. Perceived social support (PSS) and general self-efficacy (GSE) affect HL. However, the effects of PSS and GSE on walking in patients with chronic diseases remain unclear. This study, grounded in the Capability, Opportunity, and Motivation-Behavior (COM-B) model, aimed to investigate the effects of PSS, GSE, and HL on walking in patients with chronic diseases.MethodsA total of 1,550 Chinese patients with chronic diseases were included in the analysis from the 2021 Chinese Residents’ Psychological and Behavioral Survey (PBICR), a cross-sectional survey. A multistage sampling approach was implemented at both provincial and municipal levels, complemented by quota sampling based on gender, age, and urban–rural distribution. Data were collected using a structured questionnaire, the Health Literacy Scale Short Form, the New General Self-Efficacy Scale, and the Perceived Social Support Scale. Descriptive and correlation analyses were conducted with SPSS 26.0. The mediating effect of HL on the relationship between PSS, GSE, and walking was analyzed with AMOS 21.0.ResultsHL (β = 0.198, p < 0.001) significantly influenced walking. HL entirely mediated the effect of GSE on walking [β = 0.060, 95% CI = (0.040–0.082)]. HL partially mediated the effect of PSS on walking [β = 0.043, 95% CI = (0.026–0.061), effect size ratio = 21.50%].ConclusionHL is crucial for promoting walking in patients with chronic diseases. Enhancing HL through PSS and GSE effectively promotes walking in individuals with chronic diseases.